PROBLEMS WITH INTEGRAL AND BITSADZE-SAMARSKY CONDITION FOR A SECOND-ORDER PARABOLIC-HYPERBOLIC EQUATION WITH A SINGULAR COEFFICIENT (Scientific journal of the Fergana State University, 2023)
In the work, non-classical problems with an integral condition in a parabolic subdomain and the Bitsadze-Samarsky condition in a hyperbolic subdomain for a parabolic-hyperbolic equation with a singular coefficient have been formulated and investigated. The unique solvability of the considered problems was proved by the method of integral equations. In this case, the formulas for solution to the modified Cauchy problem for a hyperbolic equation with a singular coefficient and the solution of the first boundary value problem for a parabolic equation were used.